Biological attribute and disease resistance of catfish Clarias gariepinus (Burchell 1822) supplemented with different rations of spirulina Arthrospira platensis - Mohd Nasir, Nor Fatihah (2017)
Spirulina Arthrospira platensis is practically used as a supplement in nutrition due to its high nutritional content. Improving the feed formulation by combining the commercial fish feed with spirulina to the cultured fish might elevate the fish growth performance, nutritional value and increase its resistance towards bacterial infection. This study was conducted to determine the growth performance, nutritional value and disease resistance of catfish Clarias gariepinus (Burchell 1822) supplemented with different ration of spirulina, A. platensis. Five experimental diets were prepared by varying the percentage of spirulina in the fish feed containing 0% (control), 1%, 3%, 5% and 7% respectively of locally grown spirulina. A total of 30 fry (2.62±0.04gof fish initial total body weight; 7.09±0.05 cm of total body length) were stocked per cage and in triplicate. Each diet was fed to the fry twice daily at 5% of fish body weight for 90 consecutive days. Growth performances were determined every fortnight. The proximate analysis of spirulina, experimental diets and catfish fillet was done according to the method of AOAC, 1990. The catfish were then intraperitoneally injected with 107 CFU/ml of virulent Aeromonas hydrophila on day 91, and monitored until day 104. Catfish with diet of 7% spirulina produced significantly higher (p<0.05) in weight gain and specific growth rate compared to control, but not with other treatment groups. Standard length, percent of survival, feeding efficiency of the catfish increased with the increasing percentage of spirulina inclusion but was not significantly different (p>0.05) between all the diet groups. The feed conversion rate marginally decreased as spirulina inclusion increased in the diet, but not significantly different (p>0.05) between all the treatment groups. The gonado somatic index value was the highest in catfish with diet 7% spirulina but not significantly different (p>0.05) between all the treatment groups. The hepatosomatic index and viscerosomatic index value were also not significantly different (p>0.05) between all the treatment groups. The proximate compositions of the locally grown dried spirulina showed the highest content was the crude protein with 63.07±0.02% (p<0.05) followed by the carbohydrate content, ash, moisture, crude lipid and lastly crude fiber. Generally, as the percent of spirulina in the diet increase the proximate composition of the experimental diets were significantly increased (p<0.05) for the crude protein and significantly lower (p<0.05) for the crude fiber content. The moisture, ash, crude lipid and carbohydrate showed no significant (p>0.05) different between all the experimental diet groups. The content of proximate composition of catfish fillet showed at par to the control group with no significant different (p>0.05) between all diet groups except the crude fiber content that were significantly increased (p<0.05) with increasing percent of spirulina until at maximum of 3% of spirulina inclusion and there was no significant different (p>0.05) at 5% and 7% of spirulina diet. The percentage of catfish survive following A. hydrophila infection were significantly low (p<0.05) in control with 36.67% but not with other treatment groups range from 70.00% to 73.33%. The white blood cell count value was significantly higher (p<0.05) in group supplemented with 7% spirulina whereas the red blood cell, hemoglobin, packed cell volume, mean corpuscular volume, mean corpuscular hemoglobin concentration value showed no significant different between the treatment groups. This study conclude that the catfish supplemented with spirulina as low as 1% resulted in optimum disease resistance against the bacterial infection of A. hydrophila which helps in preventing mass mortality of catfish although the spirulina does not accelerate the growth performance and nutritional value of the C. gariepinus.